Self-control and its relationship to some personality traits of primary school principals. (Journal of the College of Basic Education, 2022)
The study aimed to identify the relationship of self-control with some personality traits among the principals of primary schools in Baghdad for the academic year 2015-2016. The research sample included (125) male and female principals.The researcher also adopted the personality traits scale of Raymond Cattell.The researcher chose four of them, and after processing the data using statistical methods, he reached the following results:1- The male and female managers in the research sample enjoy a good level of self-control.2- The gender variable (male - female) had no effect on causing differences in the field of self-control for male and female managers.